Large tensor-to-scalar ratio and running of the scalar spectral index with instep inflation - Ballesteros, Guillermo; Casas, J. Alberto (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
If a sizeable tensor-to-scalar ratio ∼0.1 turns out to be detected and a negative running of the scalar spectral index ∼10−2 is significantly required by the data, the vast majority of single field models of inflation will be ruled out. We show that a flat tree-level effective potential, lifted by radiative corrections and by the imprints of a high energy scale (in the form of nonrenormalizable operators) can explain those features and produce enough inflation in the slow-roll regime.
Gesehen am 29.07.2020